(untitled) (Research, Society and Development, 2022)
The antifungals used in the treatment of vulvovaginal candidiasis, although effective, can have side effects and high cost, which may not occur with the medicinal use of ozone. The study aimed to evaluate the effects of medicinal home ozone therapy on C. albicans. The experiment was carried out in vitro, cultivating C. albicans in 10mm Petri dishes, containing solid Agar Sabour and Dextrose (Oxoid). The in vivo experiment used 45-day-old female C57/BL6 mice and after suppression of ovarian activity, 20 µL of C. albicans suspension in sterile PBS, at a concentration of 105 yeast cells, were inoculated in a single dose under anesthesia. Distribution occurred in 4 groups: (i) Absolute Control Group (GCA): Not subjected to infection by the pathogen. (ii) Control Group (CG): Submitted to C. albicans infection, but not treated. (iii) Ozone Therapy Group (GO): Subjected to infection and treated with medicinal ozone therapy. (iv) Lavage Group (GL): Subjected to infection and subsequently treated with vaginal lavage. It was found that GC had a higher amount of CFU when compared to GO. Exposure for 600s was able to reduce the number of CFUs by 98.89% when compared to GC. The study concludes that ozone gas showed great efficacy in the proliferation of C. albicans in vitro. The best results were observed with application in liquid medium, however, ozone therapy was able to significantly reduce infection in the experimental model used. In in vivo experiments, the number of CFU/ml found was lower in the ozone-treated group.